2020
DOI: 10.5430/wje.v10n1p97
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in the Scholastic Achievement Test (SAT) among School Adolescents

Abstract: The paper examined gender difference in the Scholastic Achievement Test (SAT) among senior secondary school adolescents using the physical science of physics in three (3) separate papers. The paper attempted to ascertain whether gender difference accounts for the score differential observed in the Scholastic Achievement Test (SAT). The study adopted a field experiment and a sample size of 410 respondents consisting of 208 males and 202 females respectively. The correlation matrix of the three (3) papers was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…The finding in this study however, support Akpor and Egbule (2020) who carried out a study among secondary school students and found that males scored higher in three Physics papers than females with the scores widening from one paper to the other in Scholastic Achievement Test (SAT). Akpor and Egbule (2020) explained that the test scores widened in favour of males as the test papers became relatively more difficult.…”
Section: Research Question: What Correlation Exists Between Class Att...supporting
confidence: 78%
See 1 more Smart Citation
“…The finding in this study however, support Akpor and Egbule (2020) who carried out a study among secondary school students and found that males scored higher in three Physics papers than females with the scores widening from one paper to the other in Scholastic Achievement Test (SAT). Akpor and Egbule (2020) explained that the test scores widened in favour of males as the test papers became relatively more difficult.…”
Section: Research Question: What Correlation Exists Between Class Att...supporting
confidence: 78%
“…The finding in this study however, support Akpor and Egbule (2020) who carried out a study among secondary school students and found that males scored higher in three Physics papers than females with the scores widening from one paper to the other in Scholastic Achievement Test (SAT). Akpor and Egbule (2020) explained that the test scores widened in favour of males as the test papers became relatively more difficult. Cortright et al (2011) found that the influence of regular class attendance on academic performance was more important for female students than male students: female students scoring above-average grades had higher class attendance scores than female students who scored grades below class average but these differences were not observed among male students.…”
Section: Research Question: What Correlation Exists Between Class Att...supporting
confidence: 78%
“…In effect, they exhibited commendable performance in science classes. A previous study conducted by Akpotor and Egbule (2020) revealed that gender difference exists in the scholastic achievement test (SAT) between male and female senior high school learners in their physical science subject. However, their results indicate that male students outperformed their female counterpart, contrary to the present study finding.…”
Section: Science Performance Of Learners By Sex and Scholarship Statusmentioning
confidence: 99%
“…The extant literature has reported that female students exhibit better grades in school regardless of the subject matter [18], whereas males perform better on standardized tests, especially when these tests measure quantitative scientific competencies [39,40]. Null gender differences or declines in the magnitude of the differences in standardized tests have also been reported [41,42].…”
Section: Discussionmentioning
confidence: 99%